The Macroeconomy After Tariffs - Furceri, Davide; Hannan, Swarnali A.; Ostry, Jonathan D.; Rose, Andrew K. (World Bank, Washington, DC, 2021)
What does the macroeconomy look like in the aftermath of tariff changes This paper estimates impulse response functions from local projections using a panel of annual data that spans 151 countries over 1963–2014. Tariff increases are associated with persistent, economically and statistically significant, declines in domestic output and productivity, as well as higher unemployment and inequality, real exchange rate appreciation and insignificant changes to the trade balance. Output and productivity impacts are magnified when tariffs rise during expansions and when they are imposed by more advanced or smaller (as opposed to developing or larger) economies; effects are asymmetric, being larger when tariffs go up than when they fall. While firmly establishing causality is always a challenge, the results are robust to a large number of perturbations to the baseline methodology, and hold using both macroeconomic and industry-level data.